English Teacher Style in English Language Teaching - Simanjuntak, Grace Natalia Roma Uli; Aisyah, Siti (Universitas Batanghari Jambi, 2024)
This study aims to analyze the interactions between teachers and students in the twelfth grade at Senior High School 8 Jambi. The study uses a qualitative research design and a descriptive qualitative research approach. The research instruments used in this study were observation and a questionnaire. The data were acquired by giving a questionnaire to the students and observing the interaction between the teacher and the students. The research used the technique to analyze data reduction, data display, and make conclusions. According to the statistics, 63.6% of students frequently paid attention to the teacher's explanation. Furthermore, 33.3% of students stated that they sometimes feel comfortable studying in class. Finally, 27,3% of students reported feeling bored with the learning methods.